2011
DOI: 10.1523/jneurosci.1440-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hyperosmotic Stress Converts GABAergic Inhibition into Excitation in Vasopressin and Oxytocin Neurons in the Rat

Abstract: In mammals, the increased secretion of arginine-vasopressin (AVP) (antidiuretic hormone) and oxytocin (natriuretic hormone) is a key physiological response to hyperosmotic stress. In this study, we examined whether chronic hyperosmotic stress weakens GABA A receptor-mediated synaptic inhibition in rat hypothalamic magnocellular neurosecretory cells (MNCs) secreting these hormones. Gramicidin-perforated recordings of MNCs in acute hypothalamic slices prepared from control rats and ones subjected to the chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 47 publications
(54 reference statements)
4
86
2
1
Order By: Relevance
“…We developed this hypothesis, in part, because of our earlier work that demonstrated that the polarity of GABA A receptor-mediated transmission in AVP neurons can reverse in response to physiological need. 19 AVP neurons in PVN and SON are heavily innervated by GABAergic afferents, 12 which seem to originate from the perinuclear zones in the adjacent hypothalamus 12,38,39 and are stimulated by high-salt intake. 40 In the present study, we found that in AVP neurons of DOCA-salt hypertension model rats GABAergic input evoked depolarizing excitatory responses and that the excitatory action of GABA increased blood pressure by promoting AVP release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We developed this hypothesis, in part, because of our earlier work that demonstrated that the polarity of GABA A receptor-mediated transmission in AVP neurons can reverse in response to physiological need. 19 AVP neurons in PVN and SON are heavily innervated by GABAergic afferents, 12 which seem to originate from the perinuclear zones in the adjacent hypothalamus 12,38,39 and are stimulated by high-salt intake. 40 In the present study, we found that in AVP neurons of DOCA-salt hypertension model rats GABAergic input evoked depolarizing excitatory responses and that the excitatory action of GABA increased blood pressure by promoting AVP release.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from our laboratory showed that a long-term intracerebroventricular administration of selective oxytocin receptor antagonist partially blocked the NKCC1-dependent depolarizing E GABA shift and the resultant emergence of GABAergic excitation in the MNCs of rats subjected to chronic hyperosmotic stress. 19 Meanwhile, the KCC2 downregulation in DOCA-salt-treated rats might arise from the action of brain-derived neurotrophic factor released locally from glia or neurons in PVN and SON. Tropomyosinreceptor-kinase B as well as brain-derived neurotrophic factor mRNA and protein, are present in SON, 48,49 and hyperosmotic stimulus increases the local release of brain-derived neurotrophic factor in SON.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the initial stages, this effect would remove entirely a potential source of inhibition under conditions where maximal AP firing and hormone release are required. Moreover, a recent study has shown that chronic salt-loading induces a positive shift of the E Cl (Kim et al, 2011). The potential danger of this effect lies where an excitatory GlyR tone may emerge after acute rehydration, establishing a positive feedback process whereby an inappropriate rise in VP/OT release would lead to lifethreatening hyponatremia.…”
Section: Functional Role Of Taurinergic Gliotransmission In Sonmentioning
confidence: 99%
“…In principle, this negative feedback regulation of MNCs should mitigate the involvement of circulating VP in the development of hypertension. However, a recent study has shown that rat MNCs display a collapse in the transmembrane chloride (Cl − ) gradient required for inhibitory GABA A R signaling after chronic salt loading (Kim et al, 2011). A similar effect can be induced by a high-salt diet in uni-nephrectomized rats treated with deoxycorticosterone acetate (DOCA), where a weakening of BR-mediated inhibition is also associated with a VP-dependent increase in BP (Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%